STIGMATIZATION OF PSYCHIATRIC PATIENTS AMONG STUDENTS IN SERBIA - Nikolic, Gordana Miodrag; Stanojković, Maja; Žikić, Olivera; Krstić, Miroslav; Stojanović, Nikola; Tošić Golubović, Suzana; Simonović, Maja; Kostić, Jelena (Acta medicae Medianae, 2020)
ABSTRACT Social psychiatry emphasizes the inclusion of mentally ill persons in family and social life. The negative attitude towards them is still an obstacle for achieving the best treatment results and their optimal quality of life. Young educated people could be an important community factor in the fight against stigmatization of psychiatric patients. The aim of the study was to determine the difference in attitudes among Serbian students attending different faculties, as well as to find out the correlation between students' attitudes and their demographic characteristics. The study involved 408 Serbian university students. The respondents were divided into three groups to determine the differences in attitudes between groups with different educational levels. We have used the Attitude Questionnaire and Demographic Questionnaire for this purpose. Medical students who had passed their exam in psychiatry, those who experienced psychological and psychiatric problems themselves, and those with a mantally ill familly member had a positive attitude towards the mentally ill. Future health workers and the family members of mentally ill individuals are most important in the attempts to decrease stigmatization of psychiatric patients. Key words: stigmatization, students, psychiatric patients
Keywords: Key words: stigmatization, students, psychiatric patients